Modeling and simulation of compositional engineering in SiGe films using patterned stress fields. Issue 1 (5th May 2016) - Kaiser, Daniel; Ghosh, Swapnadip; Han, Sang M.; Sinno, Talid
Abstract : Semiconductor alloys such as silicon–germanium (SiGe) offer attractive environments for stress-driven compositional engineering of quantum-confined structures that are the basis for a host of current and future optoelectronic devices. Abstract : Semiconductor alloys such as silicon–germanium (SiGe) offer attractive environments for engineering quantum-confined structures that are the basis for a host of current and future optoelectronic devices. Although vertical stacking of such structures is routinely achieved via heteroepitaxy, lateral manipulation has proven much more challenging. We have recently demonstrated that a patterned elastic stress field applied, with an array of nanoscale indenters, to an initially compositionally uniform SiGe substrate will drive atomic interdiffusion leading to compositional patterns in the near-surface region of the substrate. While this approach may offer a potentially efficient and robust pathway to producing laterally ordered arrays of quantum-confined structures, optimizing it with respect to the various process parameters, such as indenter array geometry, annealing history, and SiGe substrate thickness and composition, is highly challenging. Here, a mesoscopic model based on coarse-grained lattice kinetic Monte Carlo simulation is presented that describes quantitatively the atomic interdiffusion processes in SiGe alloy films subjected to applied stress. We first show that the model provides predictions that are quantitatively consistent with experimental measurements. Then, the model is used to investigate the impact of several process parameters such as indenter shape and pitch. We find that certain indenter configurations produce compositional patterns that are favorable for engineering lateral arrays of quantum-confined structures.